Collaterals and extent of myocardial injury in patients with acute coronary syndromes – an analysis of the prospective SPUM-ACS cohort. (3rd October 2022) - Obeid, S; Adjibodou, B; Denegri, A; Kraler, S; Katsarov, K; Roffi, M; Raeber, L; Muller, O; Staehli, B; Luescher, T F
Abstract: Introduction: The impact of collateral circulation in the presence of severe coronary artery disease such as chronic total occlusion (CTO) has been extensively studied, with results despite few discrepancies, supporting an overall benefit on preservation of myocardial tissue and left ventricular ejection fraction (LVEF). However, less is known about the protective effects of collaterals in the context of acute coronary syndromes (ACS). In the current study we sought to analyze the incidence, grade and impact of collateral circulation in a large prospectively recruited cohort of patients presenting with ACS with independent events adjudication. Methods and results: 4'546 ACS patients presenting with ACS, enrolled in the prospective Special Program University Medicine ACS (SPUM-ACS) cohort were included. The current analysis showed the presence of a collateralized culprit lesion in 12.9% (n=586) of patients, 84% (n=492) originating from the contralateral side and 16% (n=94) from the ipsilateral side. Of those 64.6% (n=378) were being graded as Rentrop 2 or more. There were no differences in baseline characteristics between the two groups including incidence of diabetes, coronary artery disease, age and gender. However, despite the presence of collaterals graded Rentrop 2 or more, those patients had a significantly lower LVEF mean 48, 44% vs 51.6%, p=0.025 and higher creatinine Kinase levels, mean (CK) 981 U/I vs 957 UI, p<0.001 as compared to patients with absent collateral-circulation on admission. Interestingly a sub analysis of the STEMI population showed no significant differences in both LVEF and CK at presentation, while troponin (TNT) plasma levels were significantly lower in patients with collaterals (mean TNT 0.0031 ug/l vs 0.035 ug/l p=0.001). Additionally no differences in cardiovascular mortality, stent thrombosis or MI was seen at one year follow-up. Conclusion: The current analysis highlights a possible protective impact of a pre-existing collateral circulation against myocardial injury in the setting of ACS and ST elevation myocardial infarction. However this was not translated into improvement in hard outcomes acutely and up to one year of follow up, but may be important in the long run. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Swiss National Research Foundation - ZurichHeart House